Effect of probiotic strain addition on digestive organ growth and nutrient digestibility in growing pigs (2016)
Pigs are exposed to different types of stress. The growth-promoting antibiotics (GPA) used to counteract this stress generate residues in the final product and antibiotic-resistant microorganisms to the environment and humans. As an alternative to GPA, probiotic bacteria have been used to provide health benefits to these animals. This study aimed to determine the comparitive effect of probiotic strain additionon digestive organ growth and nutrient digestibility in growing pigs. Eighty piglets weaned at 21 days were fed two diets: a commercial diet with and without antibiotics added. Different probiotics were added to the drinking water for pigs fed the antibiotic-free diets (Lactobacillus casei, Lactobacillus acidophilus or Enterococcus faecium). Thirty-five piglets were slaughtered sequentially at days 1, 15 and 30 postweaning,and their digestive organs were extracted. Feces were also sampled by rectal collection at days 15, 30 and 45 post-weaning, in order to estimate apparent nutrient digestibility coefficients (indigestible marker). A significant increase was observed in the weight and development of digestive organs and in the nutrient digestibility percentages, especially for calcium and phosphorus, when comparing the animals that consumed E. faecium with those that consumed antibiotics. The addition of probiotic strains (especially E. faecium) can be considered as an alternative to the use of GPA when these strains are administered in pig diets during critical stages of their growth (post-weaning), since they improve thedigestibility of economically and environmentally important nutrients including calcium and phosphorus, thus decreasing their release into the environment.